Biological resources utilization in grebeg maulud ceremony in Surakarta City, Indonesia (Asian Journal of Ethnobiology, 2024)
Abstract. Ayuningtyas HR, Nabila I, ‘Azizah HPN, Andewi LC, Saensouk S, Setyawan AD. 2024. Biological resources utilization in grebeg maulud ceremony in Surakarta City, Indonesia. Asian J Ethnobiol 7: 43-49. Indonesia is a country of diverse nature, culture, and traditions in each region. Implementing traditional ceremonies is closely related to utilizing natural resources, both plants and animals, in the surrounding area. The sekaten or grebeg maulud is a ceremony which is often held every month of Rabi'ul Awal, involves gunungan elements in the form of crops contested by the community. This research was conducted in Surakarta City, Central Java, Indonesia, from November to December 2023, in Mojosongo Village, Keprabon Village, and Baluwarti Village. This study aims to determine the understanding of the community regarding the grebeg maulud ceremony, identify the biodiversity used in grebeg maulud, and determine the utilization of these resources in people's lives. The methods used in this research are survey methods, group discussions, ethnographic studies, key informant interviews, and the surrounding community interviews. The important thing that becomes the basis of this research is the utilization of crops by the surrounding community, which is calculated using the Index of Cultural Significance (ICS) value calculation. People in Mojosongo, Keprabon, and Baluwarti Villages utilize several species for grebeg maulud activities, including 2 species of fauna and 19 species of flora. The parts of the fauna utilized are eggs and meat; the most utilized part of the flora is the fruit.
Keywords: Grebeg maulud, gunungan, natural resources, tradition, utilization